Compositional and Contextual Associations of Social Capital and Fear of Crime. Issue 6 (3rd June 2021) - Han, Sehee
ABSTRACT: This study examines the association between individual and district levels of social capital and fear of crime using multilevel analysis. The study uses the 2011 Seoul Survey. Three-level random intercept models were conducted. This study found that only generalized trust in others at the individual level was associated with fear of crime. The current study further compared the variance in fear of crime attributable to the individual, household, and district levels using the intraclass correlation coefficient. The results show that a relatively large proportion of variance in fear of crime can be attributed to the household level, while only a small proportion of variance can be attributed to the district level. The results suggest that it is worth investigating household-level variables in-depth to better explain the fear of crime. Furthermore, the results indicate that social interventions lowering fear of crime are unlikely to be efficient if they target the district level only.